Integrating Climate Change Education into Secondary School English Lessons: A Project-Based Approach Using Trade Books - Masitoh Masitoh; Sary Silvhiany; Rita Inderawati (Faculty of Culture, Management, and Business Universitas Pendidikan Mandalika (UNDIKMA), 2025)
As the urgency of addressing climate change and promoting environmental sustainability continues to rise, educational institutions play a crucial role in equipping students with the knowledge and skills necessary for responsible citizenship. Recognizing the need for innovative teaching strategies in this area, this study investigates the integration of trade books into secondary school English lessons to enhance students' understanding of these pressing global issues. This study employed a design-based research (DBR) approach to develop and implement a project-based climate change education program integrated into English Language Teaching (ELT) for junior high school students. Conducted at the Public Junior High School Lalan, a remote area in South Sumatra, the study aimed to enhance students' climate literacy by exploring their existing knowledge, addressing climate change topics in the classroom, and identifying challenges in the implementation process. A total of 52 ninth-grade students, selected through purposive sampling, participated in the study. Data were collected through surveys and in-depth interviews conducted before and after the intervention. The interviews explored students’ experiences, perspectives, and changes in understanding related to climate change. Thematic analysis was used to analyze the interview transcripts, revealing shifts in students’ awareness and knowledge. The findings indicate that integrating climate change education into ELT through a project-based approach can effectively support students’ climate literacy and contribute to a more sustainable mindset among learners.